Clostridium novyi infection: a fatal association with injecting drug users. Issue 2 (1st March 2001) - Ryan, J M; Paul, J; Curtis, S; Patel, N K
Abstract : Injecting drug users frequently use accident and emergency (A&E) departments to access emergency care for local and systemic infections. Clostridium novyi type A is a bacterium that has recently been associated with a number of fatalities among drug injecting addicts. The clinical course is described of a patient who attended an A&E department with septicaemia who was found at postmortem examination to have been infected with Clostridium novyi type A. Doctors working in A&E departments should be aware of the existence of this infection and be vigilant when treating injecting drug users with localised infection.